Relationship on the Ability of Entrepreneurship Teachers in Giving Strengthening with Students Entrepreneurial Attitudes - Habibi, Beni; Hapsari, Ira Maya; Hamzani, Achmad Irwan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
It is impossible to achieve competence without directly involving it in learning. A teacher must be able to plan lessons that encourage students to participate in the learning process actively. One of the things that is encouraged is that the ability of entrepreneurship teachers to provide reinforcement is one of the skills that must be mastered to form students' entrepreneurial character. This study aims to determine the relationship between the ability of entrepreneurship teachers to reinforce the entrepreneurial attitudes of class XI students of SMIK N 1 Slawi Academic Year 2020-2021. The approach used in this research is quantitative. The population in this study were all class XI students of SMIK N 1 Slawi in the academic year 2020/2021, with 128 students divided into four classes. Data collection techniques are the methods used in collecting research data. The research techniques used are questionnaires and documentation techniques. The data analysis technique used descriptive analysis and correlation analysis. The results of the descriptive analysis show that the average ability of entrepreneurship teachers to provide reinforcement is in the high category, while entrepreneurial attitudes are in the supportive category, and there is a positive relationship between the ability of entrepreneurship teachers and students' entrepreneurial attitudes.